"Djeneba" a Minyanka Women of Southern Mali - Diallo, Bata (Journal of Anthropological Films, 2020)
Djeneba is a mother of nine children living in Kadioloko, southern Mali. Since her husband left the family some years ago Djeneba and her children manage the family’s millet fields without him. Recently the eldest boy, Madou, has brought his new wife, Lidy, into the family group. In this film we explore daily life in the compound as Djeneba assumes full responsibility for her family’s needs. Filmmaker, Bata Diallo, herself a Malian, engages Djeneba’s life-world in observational style and by way of intimate conversations. As well as the family we meet Nono, the old chief of Kadioloko. He’s a good friend of Djeneba and a renowned local philosopher with a wry world-view and a sense of humour to match. Djeneba and her family are from the agriculturalist Minyaka ethnic group but we also get to know some Fulani pastoralists who share the village of Kadioloko. “Djeneba” is an hour-long chronicle of quotidian life in rural Mali from a woman’s point of view.